Exploiting Zebrafish Xenografts for Testing the in vivo Antitumorigenic Activity of Microcin E492 Against Human Colorectal Cancer Cells - Varas, Macarena A.; Muñoz-Montecinos, Carlos; Kallens, Violeta; Simon, Valeska; Allende, Miguel L.; Marcoleta, Andrés E.; Lagos, Rosalba (Frontiers in Microbiology, 2020)
One of the approaches to address cancer treatment is to develop new drugs not only to obtain compounds with less side effects, but also to have a broader set of alternatives to tackle the resistant forms of this pathology. In this regard, growing evidence supports the use of bacteria-derived peptides such as bacteriocins, which have emerged as promising anti-cancer molecules. In addition to test the activity of these molecules on cancer cells in culture, their in vivo antitumorigenic properties must be validated in animal models. Although the standard approach for such assays employs experiments in nude mice, at the initial stages of testing, the use of high-throughput animal models would permit rapid proof-of-concept experiments, screening a high number of compounds, and thus increasing the possibilities of finding new anti-cancer molecules. A validated and promising alternative animal model are zebrafish larvae harboring xenografts of human cancer cells. Here, we addressed the anti-cancer properties of the antibacterial peptide microcin E492 (MccE492), a bacteriocin produced by Klebsiella pneumoniae, showing that this peptide has a marked cytotoxic effect on human colorectal cancer cells in vitro. Furthermore, we developed a zebrafish xenograft model using these cells to test the antitumor effect of MccE492 in vivo, demonstrating that intratumor injection of this peptide significantly reduced the tumor cell mass. Our results provide, for the first time, evidence of the in vivo antitumoral properties of a bacteriocin tested in an animal model. This evidence strongly supports the potential of this bacteriocin for the development of novel anti-cancer therapies.